Penyuluhan dan Inovasi Sanitasi Lingkungan untuk Pencegahan Salmonellosis pada Pekerja Peternakan Ayam Indi Telur - Indriani Indriani; Fransiska Julian; Luvita Puspitasari; Salwa Fathia Azzahra; Barkah Kurniawan (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
This community service activity aimed to improve the knowledge of poultry farm workers regarding salmonellosis through health education and sanitation innovation. The activity was conducted at an Indi Telur poultry farm in Tasikmalaya involving 30 workers. The method used was Communication, Information, and Education (CIE) through lectures supported by poster media and the implementation of a sanitation corner. Data were collected using pre-test and post-test instruments to measure participants’ knowledge levels. The results showed that 23 participants (76.7%) experienced an increase in knowledge, while 7 participants (23.3%) had unchanged scores, with no decrease observed. Statistical analysis using the paired sample t-test indicated a significant difference between pre-test and post-test scores (t = -10.933; p-value = 0.001). These findings indicate that the educational intervention was effective in improving participants’ understanding of salmonellosis. The integration of lecture methods with visual media and practical sanitation facilities can serve as an effective strategy in promoting occupational health behavior among poultry farm workers.